2021
DOI: 10.1080/07391102.2021.1871958
|View full text |Cite
|
Sign up to set email alerts
|

Enfuvirtide, an HIV-1 fusion inhibitor peptide, can act as a potent SARS-CoV-2 fusion inhibitor: an in silico drug repurposing study

Abstract: Regarding the urgency of therapeutic measures for coronavirus disease 2019 (COVID-19) pandemic, the use of available drugs with FDA approval is preferred because of the less time and cost required for their development. In silico drug repurposing is an accurate way to speed up the screening of the existing FDA-approved drugs to find a therapeutic option for COVID-19. The similarity in SARS-CoV-2 and HIV-1 fusion mechanism to host cells can be a key point for Inhibit SARS-CoV-2 entry into host cells by HIV fusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 75 publications
0
15
0
Order By: Relevance
“…The biophysical studies showed a significant interaction between T20 and a SARS-CoV HR1-derived peptide, suggesting that T20 could inhibit the fusion of SARS-CoV with the target cells but its effect is not strong enough for application [ 22 ]. Very recently, an in silico drug repurposing study showed that the interaction between T20 and SARS-CoV-2 S protein was remarkably stable and caused the S2 protein residues to undergo the fewest fluctuations, thus proposing T20 as potent SARS-CoV-2 fusion inhibitor with the potential to enter the clinical trial phase of COVID-19 [ 25 ]. However, the previous studies were primarily based on the bioinformatics approaches and lacked experimental evidence.…”
Section: Discussionmentioning
confidence: 99%
“…The biophysical studies showed a significant interaction between T20 and a SARS-CoV HR1-derived peptide, suggesting that T20 could inhibit the fusion of SARS-CoV with the target cells but its effect is not strong enough for application [ 22 ]. Very recently, an in silico drug repurposing study showed that the interaction between T20 and SARS-CoV-2 S protein was remarkably stable and caused the S2 protein residues to undergo the fewest fluctuations, thus proposing T20 as potent SARS-CoV-2 fusion inhibitor with the potential to enter the clinical trial phase of COVID-19 [ 25 ]. However, the previous studies were primarily based on the bioinformatics approaches and lacked experimental evidence.…”
Section: Discussionmentioning
confidence: 99%
“…By emerging of a global epidemic, many researchers sought to make it effective prevention and treatment strategies against COVID-19 using in silico , in vitro, and in vivo studies [ 25 ]. Regarding this pandemics, in silico methods have been used in different studies for analyzing the molecular structures of SARS-CoV-2 and even introducing potential therapeutic agents [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that HR1 and HR2 both in S2 unit can interact with each other to form 6-HB, which helps to bring the viral and cellular membranes in close proximity for viral fusion/entry process ( Ahmadi et al, 2021 ). Therefore, they have become important target sites for inhibition against specific CoVs.…”
Section: Cellular Entry Inhibitorsmentioning
confidence: 99%